Approaches to the Modulation of Abdominal Pain - Emeran A Mayer; Tony Lembo; Lin Chang (Canadian Journal of Gastroenterology)
Despite their high prevalence and significant economic impact on the health care system, functional gastrointestinal disorders have evaded successful therapy. Conventional medical therapies are based on inadequate disease models, and the great majority of published treatment trials are flawed in their design, permitting no conclusions to be drawn about the true efficacy of any particular treatment. During the past several years, a new, comprehensive disease model based on alterations in brain-gut interactions has rapidly evolved. Even though the precise mechanisms and sites underlying these alterations remain incompletely understood, plausible targets for the development of effective pharmacological treatments are receptors on peripheral terminals of visceral afferent nerves (opioids and serotonin), ion channels and receptors on dorsal horn neurons within the spinal cord (opioids, glutamate, calcitonin gene-related peptide and neurokinin-1), and supraspinal targets in the brainstem within the limbic system and in the prefrontal cortex (serotonin, catecholamines, dopamine and acetylcholine). Regardless of the primary pathophysiology underlying functional gastrointestinal disorders (ie, central versus peripheral), different pharmacological strategies targeted at different sites in the periphery or within the central nervous system may become effective therapies in the future.